Pelaku Kawin Tangkap Dapat di Pidana Berdasarkan Undang-Undang Tindak Pidana Perdagangan Orang - Maharany, Rambu; Rosando, Abraham Ferry (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Bride kidnapping is a customary practice that still occurs in Sumba, East Nusa Tenggara. Although considered part of tradition, this practice often involves elements of coercion and abduction of women, which contradict national and international legal principles. This study aims to analyze whether perpetrators of bride kidnapping can be prosecuted under Law Number 21 of 2007 concerning the Eradication of Human Trafficking Crimes (TPPO). This research employs a normative legal method with a statutory and conceptual approach. The findings indicate that bride kidnapping can fulfill the elements of human trafficking crimes, particularly in terms of exploitation, abuse of power, and coercion of victims. Additionally, bride kidnapping can be categorized as abduction under Article 328 of the Indonesian Criminal Code (KUHP).